Effects of acute normovolemic hemodilution and allogeneic blood transfusion on postoperative complications of oral and maxillofacial flap reconstruction: a retrospective study - Wenhao Li; Xueer Li; Yanhong Chen; Yanling Li; Rui Chen; Ziqin Kang; Zhiquan Huang; Yili Zhao (BMC, 2024)
Abstract Objective Patients undergoing oral and maxillofacial flap reconstruction often need blood transfusions due to massive blood loss. With the increasing limitations of allogeneic blood transfusion (ABT), doctors are considering acute normovolemic hemodilution (ANH) because of its advantages. By comparing the differences in the (Δ) blood indices and postoperative complications of patients receiving ABT or ANH during the reconstruction and repair of oral and maxillofacial tumor flaps, this study's purpose was to provide a reference for the clinical application of ANH. Methods The clinical data of 276 patients who underwent oral and maxillofacial flap reconstruction from September 25, 2017, to October 11, 2021, in the Department of Oral and Maxillofacial Surgery, Sun Yat-sen Memorial Hospital, were retrospectively analyzed. According to the intraoperative blood transfusion mode, the patients were divided into two groups: ABT and ANH. The differences in the (Δ) blood indices and the incidence of postoperative complications between the groups were analyzed. Results Among the 276 patients who had ANH (124/276) and ABT (152/276), there were no differences in (Δ) Hb, (Δ) PT, or (Δ) FIB (P > 0.05), while (Δ) WBC, (Δ) PLT, (Δ) APTT and (Δ) D-dimer were significantly different (P < 0.05). The blood transfusion method was not an independent factor for flap crisis (P > 0.05). The wound infection probability in patients with high post-PTs was 1.953 times greater than that in patients with low post-PTs (OR = 1.953, 95% CI: 1.232 ∼ 3.095, P = 0.004). A normal or overweight BMI was a protective factor for pulmonary infection, and the incidence of pulmonary infection in these patients was only 0.089 times that of patients with a low BMI (OR = 0.089, 95% CI: 0.017 ∼ 0.462). Moreover, a high ASA grade promoted the occurrence of pulmonary infection (OR = 6.373, 95% CI: 1.681 ∼ 24.163). The blood transfusion mode (B = 0.310, β = 0.360, P < 0.001; ANH: ln hospital stay = 2.20 ± 0.37; ABT: ln hospital stay = 2.54 ± 0.42) improved the length of hospital stay. Conclusion Preoperative and postoperative blood transfusion (Δ) Hb, (Δ) PT, and (Δ) FIB did not differ; (Δ) WBC, (Δ) PLT, (Δ) APTT, and (Δ) D-dimer did differ. There was no difference in the effects of the two blood transfusion methods on flap crisis, incision infection or lung infection after flap reconstruction, but ANH resulted in a 3.65 day shorter average hospital stay than did ABT.